PENGARUH HALAL KNOWLEDGE, ISLAMIC RELIGIOSITY, DAN HALAL LIFESTYLE TERHADAP PENILAIAN PRODUK KOSMETIK DAN KEPUTUSAN PEMBELIAN KOSMETIK HALAL - Ajeng Risdiyani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
This study aims to: (1) find out that halal knowledge has a positive and significant effect on product evaluation and purchasing decisions on halal cosmetics for Muslim consumers of generation Z; (2) find out that Islamic religiosity has a positive and significant effect on product evaluation and purchasing decisions for halal cosmetics for Muslim consumers of generation Z; (3) knowing that halal lifestyle has a positive and significant effect on product evaluation and purchasing decisions on halal cosmetics for Muslim consumers of generation Z. The research approach used in this study is a quantitative approach. This study uses the Structural Equation Modeling (SEM) method. SEM is a sophisticated cross-sectional, linear, and general statistical modeling technique. Based on the results of the research and discussion, the following conclusions can be drawn: (1) Halal knowledge has an estimated coefficient value of 0.118 and a probability value of 0.459, so that partially it is stated that it has no positive and significant effect on product evaluation and purchasing decisions for halal cosmetics in Bogor City ( survey on Muslimah Generation Z); (2) Islamic religiosity has an estimated coefficient value of 0.244 and a probability value of 0.050 so that it is partially stated to have a positive and significant effect on product evaluation and purchasing decisions for halal cosmetics in Bogor City (a survey on Muslimah Generation Z); (3) Halal lifestyle has an estimated coefficient value of 0.585 and a probability value of 0.00, so that it is partially stated to have a positive and significant effect on product evaluation and purchasing decisions for halal cosmetics in Bogor City (survey of Muslimah Generation Z).